Objek Assesmen Proses dan Hasil Belajar: Ranah Kognitif, Psikomotor dan Afektif - Feny Nida Fitriyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
In the national education system the formulation of educational objectives, both curricular and instructional objectives, uses the classification of learning outcomes from Benjamin Bloom which broadly divides it into three domains, namely: cognitive domain, affective domain, and skill domain. Based on the assessment, educators and the parent can obtain information on progress achievements to illustrate the attitudes, knowledge, and skills of the child has learning. Three aspects of the assessment of the object learning process and outcomes are also applied in early childhood education in STPPA or standards of child development achievement level formulated in core competencies, basic competencies and indicators.